The Potential Impact of High-Risk Human Papillomavirus–Negative Cervical Intraepithelial Neoplasia 2+ on Primary Human Papillomavirus Screening: A Retrospective Analysis. Issue 1 (24th July 2021) - Iacobone, Anna D; Bottari, Fabio; Guerrieri, Maria E; Vidal Urbinati, Ailyn M; Ghioni, Mariacristina; Spolti, Noemi; Pino, Ida; Passerini, Rita; Di Pace, Raffaela C; Franchi, Dorella; Preti, Eleonora P
Abstract: Objectives: To investigate the prevalence of high-risk human papillomavirus (HPV)–negative cervical intraepithelial neoplasia (CIN) and invasive cervical carcinoma (ICC) and to analyze the distribution of other genotypes in this subset. Methods: In total, 431 women who underwent excisional surgical treatment for CIN or ICC at the European Institute of Oncology, Milan, Italy, from January 2016 to December 2017 were retrospectively analyzed. The Linear Array HPV genotyping test (Roche Diagnostics) was performed on a postaliquot from high-risk-HPV–negative liquid-based cervical specimens, when available. Patient characteristics and the prevalence of high-risk-HPV–negative CIN grade 2 or worse (CIN2+) were tabulated. We used t tests to compare age between high-risk-HPV–positive and high-risk-HPV–negative patients. Results: Overall, 8.9% of CIN2+ and 7.5% of ICC cases were high-risk HPV negative. There was no age difference between high-risk-HPV–negative CIN2+ women (mean [SD], 41.3 [8.7] years) and high-risk-HPV–positive women (mean [SD], 39.5 [9.0] years) ( P = .28). The Linear Array result was available in 22 cases. Most high-risk-HPV–negative patients were positive for a single other genotype infection (32.6%). HPV 73 was the most prevalent genotype, followed by HPV 53 and HPV 84. HPV 26 was detected in 1 case of ICC. Conclusions: Our results showed a not-negligible proportion of high-risk-HPV–negative CIN2+, suggesting that cotesting would not miss these cases.